Sol-gel preparation method and application of TiO2-SiO2 photocatalyst

By loading the TiO2-SiO2 photocatalyst with TiO2 coating in the SiO2 colloidal crystal template, the problem of rhodamine B is difficult to degrade, efficient and environmentally friendly degradation of organic pollutants is achieved, and the dispersion and specific surface area of the catalyst are improved.

CN120479406APending Publication Date: 2025-08-15BENGBU COLLEGE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510615898.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-14
Publication Date
2025-08-15

AI Technical Summary

Technical Problem

In the prior art, Rhodamine B in organic wastewater is difficult to effectively degrade, resulting in serious environmental pollution, especially the common problems in the discharge of wastewater in the printing and dyeing industry in coastal cities.

Method used

Using the sol-gel preparation method of TiO2-SiO2 photocatalyst, a TiO2-SiO2 photocatalyst supported by SiO2 colloidal crystal template was prepared by loading a TiO2 coating on SiO2 spheres, and the organic pollutants were degraded using its photocatalytic activity.

Benefits of technology

It has achieved efficient degradation of rhodamine B. TiO2-SiO2 photocatalyst has good photocatalytic activity and stability, will not cause pollution to the environment, and will improve dispersion and specific surface area. It is suitable for drug carriers and paint surface coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120479406A_ABST
    Figure CN120479406A_ABST
Patent Text Reader

Abstract

The invention provides a sol-gel preparation method and application of a TiO2-SiO2 photocatalyst, and relates to the technical field of photocatalysts.The preparation method comprises the following steps that ethyl silicate serves as a silicon source, absolute ethyl alcohol and deionized water serve as solvents, and a SiO2 colloidal crystal template is prepared under the catalytic action of ammonia water; the preparation method comprises the following steps: preparing a SiO2 colloidal crystal template, adding a mixed solution obtained by hydrolysis of butyl titanate and absolute ethyl alcohol into the SiO2 colloidal crystal template, and preparing the TiO2-SiO2 photocatalyst with a TiO2 coating loaded on SiO2 spheres by adopting a sol-gel preparation technology. According to the preparation method and the application thereof provided by the invention, the preparation process is relatively simple and convenient, the reaction is easy to carry out, the prepared SiO2 microspheres are relatively good in monodispersity, controllable in size and high in purity, uniform doping on a molecular level is easy to realize, and degradation of organic pollutants can be effectively realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalysts, and in particular to a sol-gel preparation method of a TiO2-SiO2 photocatalyst and its application. Background Art

[0002] In recent years, the over-use of resources has led to serious natural pollution. The textile and printing and dyeing industry is an industry that has a great impact on environmental pollution because some organic dyes in the environment and water bodies have strong dyeing power and high radioactivity.

[0003] Rhodamine B in organic wastewater is one of the most difficult-to-degrade substances produced in industrial production. Its persistent nature and tendency to accumulate pose serious ecological risks. This is particularly prevalent in coastal cities, where wastewater from the printing and dyeing industry is a common source. Summary of the Invention

[0004] In view of the shortcomings of the prior art described above, the present invention aims to provide a sol-gel preparation method for a TiO2-SiO2 photocatalyst and its application to address the problem of Rhodamine B in organic wastewater, a refractory substance produced in large quantities in industrial production. Its persistent nature and tendency to accumulate pose serious ecological risks. This is a common problem, particularly in coastal cities, where wastewater discharged from the printing and dyeing industry is a major concern.

[0005] To achieve the above-mentioned and other related purposes, the present invention provides a sol-gel preparation method for a TiO2-SiO2 photocatalyst, comprising the following steps: using ethyl silicate as a silicon source, anhydrous ethanol and deionized water as solvents, and preparing a SiO2 colloidal crystal template under the catalytic action of ammonia water; adding a mixed solution of hydrolyzed butyl titanate and anhydrous ethanol to the SiO2 colloidal crystal template, and using a sol-gel preparation technique to prepare a TiO2-SiO2 photocatalyst with a TiO2 coating loaded on SiO2 spheres.

[0006] In one embodiment of the present invention, ethyl silicate is used as a silicon source, anhydrous ethanol and deionized water are used as solvents, and a SiO2 colloidal crystal template is prepared under the catalytic action of ammonia water, including: mixing anhydrous ethanol and deionized water evenly to obtain a solvent; adding ethyl orthosilicate to the solvent to obtain a silane solution; adjusting the pH of the silane solution to 7.0 using a pH regulator, and placing it in a water bath at a preset temperature for aging; and adding concentrated ammonia water dropwise to the aged silane solution until the silane solution is completely converted into a gel to prepare the SiO2 colloidal crystal template.

[0007] In one embodiment of the present invention, the pH of the silane solution is adjusted to 7.0 using a pH adjuster, and the solution is placed in a water bath at a preset temperature for aging, including: exchanging deionized water and an equal volume of concentrated ammonia water into an ammonia solution for pH adjustment; adjusting the pH of the silane solution to 7.0 using the pH adjuster, stirring, and placing the solution in a water bath set to a preset temperature for aging.

[0008] In one embodiment of the present invention, the pH of the silane solution is adjusted to 7.0 using a pH adjuster, stirred, and placed in a water bath set to a preset temperature for aging. The stirring time is at least 10 minutes, the preset temperature is 36° C., and the aging time is at least 1 hour.

[0009] In one embodiment of the present invention, concentrated ammonia water is added dropwise to an aged silane solution until the silane solution is completely converted into a gel to prepare a SiO2 colloidal crystal template, comprising: cooling the aged silane solution to room temperature; adding concentrated ammonia water dropwise to the cooled silane solution; and when a gel jelly-like substance is observed in the silane solution after the addition of concentrated ammonia water, allowing the solution to stand until the silane solution is completely converted into a gel to prepare the SiO2 colloidal crystal template.

[0010] In one embodiment of the present invention, a mixture of butyl titanate and anhydrous ethanol hydrolysis is prepared by the following method: adding hydrochloric acid to anhydrous ethanol and mixing uniformly to obtain an intermediate mixture; continuously adding butyl titanate to the intermediate mixture multiple times to obtain a white substance of TiO2 and n-butanol; when it is observed that no white substance is produced in the intermediate mixture, the hydrolysis is complete, and a mixture of butyl titanate and anhydrous ethanol hydrolysis is obtained.

[0011] In one embodiment of the present invention, a mixture of butyl titanate and anhydrous ethanol hydrolysis is added to a SiO2 colloidal crystal template, and a sol-gel preparation technology is used to prepare a TiO2-SiO2 photocatalyst with a TiO2 coating loaded on SiO2 spheres, comprising: adding a mixture of butyl titanate and anhydrous ethanol hydrolysis, and polyvinyl pyrrolidone to the SiO2 colloidal crystal template, sealing and stirring, and continuing to stir after ultrasonic dispersion for a set time to obtain a stable suspension; allowing the suspension to stand to obtain a stratified liquid; drying the stratified liquid, crushing and grinding it into a powder to obtain an intermediate powder; and calcining the intermediate powder at a high temperature to obtain a TiO2-SiO2 photocatalyst.

[0012] In one embodiment of the present invention, the ultrasonic dispersion setting time is at least 15 minutes, the static treatment time is at least 1 hour, the high-temperature calcination temperature is 600° C., and the high-temperature calcination time is 6 hours.

[0013] To achieve the above-mentioned and other related purposes, the present invention also provides a use of a TiO2-SiO2 photocatalyst prepared by the aforementioned sol-gel preparation method of TiO2-SiO2 photocatalyst in the degradation of dyes.

[0014] In one embodiment of the present invention, the dye is dispersed in a dye solution, the dye solution is a Rhodamine B solution, the initial concentration of the Rhodamine B solution is 8.43 mg / L, the pH value of the solution is 5.6, and the amount of the TiO2-SiO2 photocatalyst used is 0.20 g.

[0015] As described above, the sol-gel preparation method and application of a TiO2-SiO2 photocatalyst of the present invention have the following beneficial effects: The TiO2-SiO2 photocatalyst prepared by the sol-gel preparation method of the present invention enables the degradation of organic pollutants using TiO2-SiO2 photocatalyst. TiO2 has excellent photocatalytic activity and is harmless to the human body, exhibiting high photocatalytic activity, stability, and regeneration. TiO2 does not require recycling during the photocatalytic degradation process and does not pollute the natural environment, making it an excellent environmentally friendly photocatalyst. Nano-SiO2 microspheres are widely used in drug carriers, paint surface coatings, and other applications. Due to their quantum size effects, surface interface effects, and strong stability, high strength, and excellent toughness under high temperature conditions, the TiO2-SiO2 photocatalyst prepared by the preparation method of the present invention, by coating the SiO2 microspheres with a nano-scale TiO2 film, achieves a smaller particle size and a higher specific surface area, significantly improving dispersibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Shown is a flow chart of the preparation method of the present invention.

[0017] Figure 2 Shown is a schematic diagram of the XRD pattern of the TiO2-SiO2 photocatalyst of the present invention.

[0018] Figure 3 Shown is a polarizing microscope photo of the present invention.

[0019] Figure 4 Shown is the FT-IR graph of the TiO2-SiO2 microspheres of the present invention.

[0020] Figure 5 The graph shows the relationship between the adsorption time and absorbance of the RhB solution of the present invention.

[0021] Figure 6 Shown is a curve diagram showing the effect of the initial concentration of the RhB solution of the present invention on the degradation efficiency.

[0022] Figure 7 Shown is a curve diagram of the effect of pH value on degradation rate of the present invention.

[0023] Figure 8 The graph shows the effect of different TS catalyst dosages on the degradation efficiency of the present invention. DETAILED DESCRIPTION

[0024] The following describes the embodiments of the present invention through specific examples. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following examples and the features in the examples can be combined with each other unless they conflict. It should also be understood that the terms used in the examples of the present invention are for the purpose of describing specific embodiments, not for the purpose of limiting the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are generally carried out under conventional conditions or under the conditions recommended by the manufacturers.

[0025] See also Figures 1 to 8 . It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention. Therefore, they have no substantive technical significance. Any modification of the structure, change in the proportional relationship or adjustment of the size should still fall within the scope of the technical content disclosed by the present invention without affecting the efficacy and purpose that can be achieved by the present invention. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the implementation of the present invention without substantially changing the technical content.

[0026] See also Figure 1 The present invention provides a sol-gel preparation method of TiO2-SiO2 photocatalyst, comprising the following steps:

[0027] Step S10: using ethyl silicate as a silicon source, anhydrous ethanol and deionized water as solvents, and preparing a SiO2 colloidal crystal template under the catalysis of ammonia water;

[0028] Step S20: Adding a mixture of butyl titanate and anhydrous ethanol hydrolyzed therein to the SiO2 colloidal crystal template, and adopting a sol-gel preparation technique to prepare a TiO2-SiO2 photocatalyst with a TiO2 coating loaded on SiO2 spheres.

[0029] Through the above steps, it is readily apparent that the sol-gel preparation method for the TiO2-SiO2 photocatalyst of the present invention can be used to prepare a TiO2-SiO2 photocatalyst with a TiO2 coating on SiO2 spheres, thereby enabling the use of TiO2-SiO2 photocatalysts to degrade organic pollutants. TiO2 exhibits excellent photocatalytic activity, is harmless to the human body, and possesses high photocatalytic activity, stability, and reproducibility. TiO2 does not require recycling during the photocatalytic degradation process and does not pollute the natural environment, making it an excellent environmentally friendly photocatalyst. Nano-SiO2 microspheres are widely used in pharmaceutical carriers, paint coatings, and other applications. Due to their quantum size effects, surface interface effects, and strong stability, strength, and toughness under high temperature conditions, the TiO2-SiO2 photocatalyst prepared by the preparation method of the present invention, by coating the SiO2 microspheres with a nanoscale TiO2 film, achieves a smaller particle size and a higher specific surface area, significantly improving dispersibility.

[0030] In step S10, ethyl silicate is used as a silicon source, anhydrous ethanol and deionized water are used as solvents, and a SiO2 colloidal crystal template is prepared under the catalysis of ammonia water, which may further include:

[0031] Mixing anhydrous ethanol and deionized water to obtain a solvent;

[0032] adding ethyl orthosilicate to a solvent to obtain a silane solution;

[0033] The pH of the silane solution is adjusted to 7.0 using a pH regulator, and the solution is placed in a water bath at a preset temperature for aging.

[0034] Concentrated ammonia water is added dropwise to the aged silane solution until the silane solution is completely converted into gel to prepare a SiO2 colloidal crystal template.

[0035] During the solvent preparation process, anhydrous ethanol and deionized water can be mixed according to a volume ratio of 7:3, and of course other ratios can also be used. The mixed solvent is placed in a stirred vessel, and magnet is added simultaneously, and is placed in an electromagnetic stirrer and stirred to mix it. Then tetraethyl orthosilicate (TEOS) is added and stirred to obtain a silane solution, wherein, anhydrous ethanol, deionized water and tetraethyl orthosilicate can be configured according to a volume ratio of 7:3:1. After obtaining the silane solution, deionized water and concentrated ammonia are then utilized to prepare a pH adjusting agent according to a volume ratio of 1:1 and added to the silane solution to adjust the pH of the silane solution to 7.0. After the pH value is adjusted, it is placed in a water bath under a preset temperature and aged, and after aging is completed, the silane solution is fully converted into a gel using concentrated ammonia to prepare a SiO2 colloidal crystal template.

[0036] Specifically, adjusting the pH of the silane solution to 7.0 using a pH regulator and placing the solution in a water bath at a preset temperature for aging may further include:

[0037] Exchange deionized water and an equal volume of concentrated ammonia water into an ammonia solution to be used as a pH regulator;

[0038] The pH of the silane solution was adjusted to 7.0 using a pH adjuster, stirred, and placed in a water bath set to a preset temperature for aging.

[0039] Ammonia solution, prepared with a 1:1 volume ratio of deionized water and concentrated ammonia, is used as a pH adjuster. This pH adjuster is then slowly added dropwise to the silane solution, thereby adjusting the pH of the silane solution to 7.0 through the activating effect of the ammonia solution. After the pH of the silane solution reaches 7.0, the prepared silane solution is placed in a water bath at a pre-set temperature for aging.

[0040] Preferably, the pH of the silane solution is adjusted to 7.0 using a pH regulator, stirred, and placed in a water bath set to a preset temperature for aging, with the stirring time being at least 10 minutes, the preset temperature being 36° C., and the aging time being at least 1 hour.

[0041] Furthermore, concentrated ammonia is added dropwise to the aged silane solution until the silane solution is completely converted into a gel to prepare a SiO2 colloidal crystal template, which may further include:

[0042] Cooling the aged silane solution to room temperature;

[0043] Add concentrated ammonia solution dropwise to the cooled silane solution;

[0044] When a gel jelly-like substance is observed in the silane solution after adding concentrated ammonia water, the solution is allowed to stand until the silane solution is completely converted into gel to prepare a SiO2 colloidal crystal template.

[0045] After the silane solution is aged, it is cooled to room temperature and then placed on an electromagnetic stirrer. Concentrated ammonia is added dropwise to the silane solution using a rubber-tipped dropper. When a gel-like jelly-like substance is produced in the silane solution, the solution is allowed to stand until the silane solution is completely converted into a gel, thereby obtaining a SiO2 colloidal crystal template.

[0046] In step S20, a mixture of butyl titanate and anhydrous ethanol is prepared by the following method:

[0047] Add hydrochloric acid to anhydrous ethanol and mix well to obtain an intermediate mixed solution;

[0048] Continuously add butyl titanate to the intermediate mixture several times to obtain a white substance containing TiO2 and n-butanol;

[0049] When no white substance is observed to be produced in the intermediate mixed solution, the hydrolysis is completed to obtain a mixed solution of hydrolysis of butyl titanate and anhydrous ethanol.

[0050] When a mixed solution of butyl titanate and anhydrous ethanol hydrolysis is prepared, hydrochloric acid is first added to anhydrous ethanol to obtain an intermediate mixed solution. Since butyl titanate undergoes a hydrolysis reaction under the catalytic action of an acid to produce a white substance of TiO2 and n-butanol, butyl titanate can be added to the intermediate mixed solution to obtain a white substance of TiO2 and n-butanol. During the specific operation, anhydrous ethanol and hydrochloric acid can be configured according to a volume ratio of 30:1. When butyl titanate is added to the intermediate mixed solution, a pipette can be used multiple times, for example three times, and butyl titanate (TBOT) can be injected by slowly pressing to produce a white substance of TiO2 and n-butanol. When preparing a mixed solution of butyl titanate and anhydrous ethanol hydrolysis, when it is observed that butyl titanate is added to the intermediate mixed solution, no white substance is produced in the intermediate mixed solution, indicating that the hydrolysis is complete, and what is obtained now is a mixed solution of butyl titanate and anhydrous ethanol hydrolysis. In addition, the error of a single operation can be reduced by pipetting the liquid multiple times. If you pipette a large amount of liquid at once, the volume may be inaccurate due to improper operation (such as bubbles, liquid residue, etc.). Pipetting in multiple times can better control the amount of liquid pipetted each time and ensure the accuracy of the total volume.

[0051] In step S20, a mixture of butyl titanate and anhydrous ethanol hydrolyzed is added to a SiO2 colloidal crystal template, and a sol-gel preparation technique is used to prepare a TiO2-SiO2 photocatalyst having a TiO2 coating on SiO2 spheres, comprising:

[0052] Add the mixture of butyl titanate and anhydrous ethanol hydrolysis and polyvinyl pyrrolidone to the SiO2 colloidal crystal template, seal and stir, and continue stirring after the ultrasonic dispersion set time to obtain a stable suspension;

[0053] The suspension is allowed to stand to obtain a layered liquid;

[0054] Dry the layered liquid, crush and grind it into powder to obtain an intermediate powder;

[0055] The intermediate powder is calcined at high temperature to obtain a TiO2-SiO2 photocatalyst.

[0056] By SiO When the mixed solution of colloidal crystal template and butyl titanate and anhydrous ethanol hydrolysis is mixed, first by SiO Colloidal crystal template adds in the stirred vessel cleaned in advance, then stirred vessel is placed on electromagnetic stirring apparatus, add the mixed solution and polyvinylpyrrolidone (PVP) of butyl titanate and anhydrous ethanol hydrolysis simultaneously, then in stirred vessel, add after magnetite, by plastic film sealing, and on electromagnetic stirring apparatus, stir as 12 hours.Then prevent from dispersing in ultrasonic again, and be placed on the electromagnetic stirring apparatus again and continue to stir after dispersion, after waiting to form more stable suspension, leave standstill for a period of time.After leaving standstill to complete, the layering liquid that leaves standstill to complete obtaining is put into for example electric constant temperature forced air drying oven, after oven dry, take out and smash to pieces and grind to powdered, calcine with microwave muffle furnace.

[0057] Preferably, the ultrasonic dispersion setting time is at least 15 minutes, the static treatment time is at least 1 hour, the high-temperature calcination temperature is 600° C., and the high-temperature calcination time is 6 hours.

[0058] The present invention also provides an application of a TiO2-SiO2 photocatalyst prepared by the aforementioned sol-gel preparation method of the TiO2-SiO2 photocatalyst in the degradation of dyes.

[0059] Furthermore, the dye is dispersed in a dye solution, the dye solution is a Rhodamine B solution, the initial concentration of the Rhodamine B solution is 8.43 mg / L, the pH value of the solution is 5.6, and the amount of the TiO2-SiO2 photocatalyst used is 0.20 g.

[0060] In the process of preparing TiO2-SiO2 photocatalyst by the sol-gel preparation method of TiO2-SiO2 photocatalyst of the present invention, please refer to Figure 2, is the XRD spectrum of TiO2-SiO2 photocatalyst prepared by sol-gel method at different calcination temperatures and different holding times. Through energy spectrum analysis and comparison of CD line with standard card, it is observed that the CD line in the figure corresponds to crystal planes (101), (103), (004), (112), (200), (105), (211) at 2θ=25°, 37°, 38°, 39°, 48°, 53°, and 55°, respectively. Its characteristic peaks are consistent with the characteristic peaks of anatase phase (it also shows that there are more lattice defects in the anatase phase lattice, resulting in more oxygen vacancies to capture electrons, and the photocatalytic degradation effect is better). By comparing the AB line and CD line in the figure, it can be seen that the relative intensity of the characteristic peak of anatase phase is higher and the width is narrower when the calcination temperature is 600℃, indicating that the crystallinity is better and the volume fraction is large. The sample calcined at 550°C showed no anatase-type characteristic peaks at 2θ = 28°, 36°, and 41°, corresponding to the crystal planes (110), (101), and (111). This indicates that when the sample was calcined at 550°C for 4 and 6 hours, no microspheres containing TiO2 loaded on SiO2 were formed. When the sample was calcined at 600°C for 4 and 6 hours, the composite microspheres produced contained silicon, titanium, and oxygen, further demonstrating that the product contained both TiO2 and SiO2.

[0061] See also Figure 3 The polarizing microscope photographs of TiO2-SiO2 powders at different calcination temperatures and holding times show that samples synthesized at 600°C for 6h and 4h have a transparent film around each crystal. This is because TiO2 is loaded on SiO2 nanospheres. TiO2 is loaded on SiO2 as a film and has strong permeability, while SiO2 is a solid sphere with poor permeability. The crystals of the samples synthesized at 550°C for 4h and 6h are solid crystal spheres, and the crystallization effect of the microspheres at 600°C is fuller and more evenly dispersed than that at 550°C, indicating that the synthesis effect is better under this temperature.

[0062] See also Figure 4The infrared spectra of TiO2-SiO2 photocatalysts prepared at different calcination temperatures and holding times are shown. The peak around 3400 cm⁻¹ corresponds to the stretching vibration of the OH bond of water adsorbed on the TiO2 surface, while the peak around 1091 cm⁻¹ corresponds to the antisymmetric stretching vibration of the Si-O-Si bond, and the peak at 800 cm⁻¹ corresponds to the symmetric stretching vibration of the Si-O-Si bond. The characteristic absorption peaks at 400-1250 cm⁻¹ correspond to the O-Si-O skeleton, while the peak at 930 cm⁻¹ is characteristic of Ti-O-Si. The strongest absorption peak is observed when the sample is calcined at 600°C and held for 6 hours. This indicates that the core-shell structure of the TS sample prepared at 600°C is more uniform, which enhances the interaction between the active components, forming more Ti-O-Si bonds. This demonstrates that the composite TiO2-SiO2 photocatalyst was synthesized using the sol-gel method.

[0063] In a preferred embodiment of the present invention, in the process of using TiO2-SiO2 photocatalyst to conduct adsorption experiments on the degradation of Rhodamine B solution, Rhodamine B solution is used to simulate the organic soluble dye wastewater produced in industry, and the catalytic performance of the prepared TiO2-SiO2 microsphere photocatalyst is detected through photocatalytic degradation experiments. The adsorption experiment is carried out in a dark environment at 25°C. Weigh 0.00843g of Rhodamine B and add it to a 1000ml volumetric flask to make up the volume, and prepare 8.43mg / L of Rhodamine B solution. Measure 50ml of the solution in a quartz dish, put a magnet in it, turn on the electromagnetic stirrer, and connect the condenser to pass water. Then turn on the xenon lamp for irradiation, take the upper water sample for centrifugation every 10 minutes, and measure the absorbance. Test until the absorbance of the water sample no longer changes, indicating that the solution has reached adsorption equilibrium. Figure 5 The graph showing the relationship between adsorption time and absorbance of a Rhodamine B (RhB) solution shows that the absorbance of the RhB solution gradually decreases with increasing adsorption time. After 45 minutes, the absorbance of the solution stops changing, indicating that the solution concentration is no longer changing and adsorption has reached equilibrium. Therefore, the adsorption time was set at 45 minutes in this experiment.

[0064] Experimental data table:

[0065]

[0066] It can be seen from the above table that when the pH value of the same solution is 6 and the catalyst dosage is 0.15 g, with the increase of the initial RhB concentration, the degradation efficiency gradually increases to 82.5% and then gradually decreases; when the initial RhB concentration is 8.43 mg / L and the pH is 6, with the addition of the catalyst, the degradation efficiency gradually increases to 85.6% and then does not change significantly; when the initial RhB concentration is 8.43 mg / L and the catalyst dosage is 0.15 g, the degradation rate gradually increases to 84.1% and then gradually decreases.

[0067] In addition, during the experiment on the effect of different initial concentrations of Rhodamine B on the degradation efficiency, 0.00221g, 0.00421g, 0.00601g, 0.00843g, and 0.01014g of Rhodamine B were weighed on an analytical balance, added to a 1000ml volumetric flask for constant volume, and the pH of the solution was adjusted to 6. 50ml of Rhodamine B solution was measured in a quartz dish, a magnet was placed, and a magnetic stirrer was turned on for 45 minutes in a dark environment at 25°C. 0.15g of photocatalyst was added to allow Rhodamine B to be fully adsorbed on the catalyst, and a condenser was connected to pass water. Then the xenon lamp was turned on, the light was irradiated for 1 hour, the sample was centrifuged, and the supernatant was taken for absorbance measurement. Figure 6 The graph showing the effect of the initial RhB solution concentration on degradation efficiency shows that degradation efficiency increases with increasing initial RhB concentration, reaching its peak at 8.43 mg / L. This is because, under positive reaction conditions, the reaction rate increases with increasing RhB concentration before 8.43 mg / L. However, when the initial RhB concentration is too high, the RhB solution darkens in color, which reduces the number of photons absorbed by the solution during UV irradiation and weakens the degradation efficiency.

[0068] Next, in the process of conducting an experiment on the effect of different TiO2-SiO2 catalyst dosages on degradation efficiency, 0.00843 g of Rhodamine B was weighed out on an analytical balance, added to a 1000 ml volumetric flask for dilution, and an 8.43 mg / L Rhodamine B solution was obtained, and the pH of the solution was adjusted to 6. 50 ml of Rhodamine B was measured in a quartz dish, and a magnet was placed in it. 0.05 g, 0.10 g, 0.15 g, 0.20 g, and 0.25 g of TS catalyst were weighed out and added to the quartz dish. In a dark environment at 25°C, a magnetic stirrer was turned on for 45 minutes to allow Rhodamine B to be fully adsorbed on the photocatalyst, and a condenser was connected to allow water to pass through. Then the xenon lamp was turned on, and the light was irradiated for 1 hour. The sample was centrifuged and the upper clear liquid was taken for absorbance measurement. Figure 8The graph showing the effect of varying TS catalyst dosages on degradation efficiency shows that as the TS catalyst dosage increases, the degradation rate also gradually rises. However, when the catalyst dosage exceeds 0.20g, the degradation efficiency increase is minimal. This is because when a small amount of TS catalyst is first added, the photocatalytically active sites in the solution increase as the catalyst dosage gradually increases, generating numerous electron holes that absorb more photon energy, leading to significant changes in degradation efficiency. Further additions of catalyst beyond 0.20g cause the solution to become turbid, which scatters light and affects the solution's absorption of photons. This reduces the number of surface electron-hole pairs and weakens the degradation effect.

[0069] Furthermore, during the experiment on the effect of pH value of different Rhodamine B solutions on degradation efficiency, 0.00843 g of Rhodamine B was weighed out on an analytical balance, and the volume was fixed in a 1000 ml volumetric flask to prepare an 8.43 mg / L Rhodamine B solution. Sodium hydroxide and hydrochloric acid solutions were used to adjust the pH value of the Rhodamine B solution (pH was 3.0, 4.0, 5.0, 6.0, and 7.0, respectively) to test the absorbance. 50 ml of Rhodamine B solution with different pH values was measured respectively, and 0.15 g of TS photocatalyst of the same mass was added at 25 ° C in a dark environment. The magnetic stirrer was turned on for 4 minutes to allow Rhodamine B to be fully adsorbed on the photocatalyst, and the condenser was connected to allow water to pass through. Then the xenon lamp was turned on, the light was irradiated for 1 hour, the sample was centrifuged, and the upper clear liquid was taken for absorbance measurement. Figure 7 The graph showing the effect of pH on degradation rate shows that the photocatalytic degradation efficiency increases as the solution pH increases from 3.0 to 5.6. This is because Rhodamine B solution is a cationic dye, and the addition of H+ to the solution enhances the catalytic effect. The degradation efficiency reaches its highest at a pH of 5.6, but gradually decreases after that. This is because as the pH increases, the solution contains excessive Na+, which replaces the H+ in the SiO2 molecules, generating -ONa+. This inhibits the generation of photocatalytic electron-hole pairs, reduces the number of photon transfers, and leads to decreased TS (TiO2-SiO2) photocatalytic activity and degradation efficiency.

[0070] Verification test table:

[0071]

[0072]

[0073] As shown in the table above, the prepared TiO2-SiO2 photocatalyst was subjected to comparative degradation experiments against a TiO2 photocatalyst. The experimental conditions for both experiments were adjusted to an initial RhB concentration of 8.43 mg / L, a pH of 5.6, and a catalyst dosage of 0.20 g. The results showed that the prepared TS catalyst significantly outperformed the TiO2-catalyzed RhB degradation efficiency. Under these experimental conditions, the average degradation rate of rhodamine B was 86.2%, with a relative error of 0.9380%.

[0074] In summary, the present invention discloses a sol-gel preparation method for a TiO2-SiO2 photocatalyst and its application. The TiO2-SiO2 photocatalyst prepared by the present invention's sol-gel preparation method can be used to degrade organic pollutants. TiO2 exhibits excellent photocatalytic activity and is harmless to the human body, exhibiting high photocatalytic activity, stability, and regeneration. TiO2 does not require recycling during the photocatalytic degradation process and does not pollute the natural environment, making it an excellent environmentally friendly photocatalyst. Nano-SiO2 microspheres are widely used in drug carriers, paint coatings, and other applications. Due to their quantum size effects, surface interface effects, and strong stability, strength, and toughness under high temperature conditions, the TiO2-SiO2 photocatalyst prepared by the present invention, by coating the SiO2 microspheres with a nanoscale TiO2 film, achieves a smaller particle size and a higher specific surface area, significantly improving dispersibility. Therefore, the present invention effectively overcomes various shortcomings of the prior art and has high industrial utilization value.

[0075] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the present invention. Anyone skilled in the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by one of ordinary skill in the art without departing from the spirit and technical principles disclosed herein are intended to be covered by the claims of the present invention.

Claims

1. A sol-gel preparation method for a TiO2-SiO2 photocatalyst, characterized in that: The steps include: SiO2 colloidal crystal templates were prepared using ethyl silicate as silicon source, anhydrous ethanol and deionized water as solvents under the catalysis of ammonia. A mixed solution of hydrolyzed butyl titanate and anhydrous ethanol is added to the SiO2 colloidal crystal template, and a sol-gel preparation technology is adopted to prepare a TiO2-SiO2 photocatalyst with a TiO2 coating loaded on SiO2 spheres.

2. The sol-gel preparation method of TiO2-SiO2 photocatalyst according to claim 1, characterized in that: Using ethyl silicate as a silicon source, anhydrous ethanol and deionized water as solvents, and under the catalysis of ammonia water, a SiO2 colloidal crystal template is prepared, including: Mixing anhydrous ethanol and deionized water uniformly to obtain the solvent; adding ethyl orthosilicate to the solvent to obtain a silane solution; Adjusting the pH of the silane solution to 7.0 using a pH regulator and placing the solution in a water bath at a preset temperature for aging; Concentrated ammonia water is added dropwise to the aged silane solution until the silane solution is completely converted into gel, so as to prepare a SiO2 colloidal crystal template.

3. The sol-gel preparation method of TiO2-SiO2 photocatalyst according to claim 2, characterized in that: The silane solution is adjusted to pH 7.0 using a pH regulator and placed in a water bath at a preset temperature for aging, comprising: Deionized water and an equal volume of concentrated ammonia water are exchanged into an ammonia solution to serve as the pH regulator; The pH of the silane solution was adjusted to 7.0 using a pH regulator, stirred, and placed in a water bath set to a preset temperature for aging.

4. The sol-gel preparation method of TiO2-SiO2 photocatalyst according to claim 3, characterized in that: The pH of the silane solution is adjusted to 7.0 using a pH regulator, stirred, and placed in a water bath set to a preset temperature for aging. The stirring time is at least 10 minutes, the preset temperature is 36° C., and the aging time is at least 1 hour.

5. The sol-gel preparation method of TiO2-SiO2 photocatalyst according to claim 2, characterized in that: Adding concentrated ammonia water dropwise to the aged silane solution until the silane solution is completely converted into gel to prepare a SiO2 colloidal crystal template, comprising: Cooling the aged silane solution to room temperature; adding the concentrated ammonia solution dropwise to the cooled silane solution; When a gel jelly-like substance is observed in the silane solution after the concentrated ammonia solution is added, the solution is allowed to stand until the silane solution is completely converted into gel to prepare a SiO2 colloidal crystal template.

6. The sol-gel preparation method of TiO2-SiO2 photocatalyst according to claim 1, characterized in that: The mixed solution of the hydrolysis of butyl titanate and anhydrous ethanol is prepared by the following method: Adding hydrochloric acid to the anhydrous ethanol and mixing uniformly to obtain an intermediate mixed solution; Continuously adding butyl titanate to the intermediate mixed solution several times to obtain a white substance containing TiO2 and n-butanol; When it is observed that the white substance is no longer produced in the intermediate mixed liquid, the hydrolysis is completed to obtain the mixed liquid of hydrolysis of butyl titanate and anhydrous ethanol.

7. The sol-gel preparation method of TiO2-SiO2 photocatalyst according to claim 1, characterized in that: A mixture of butyl titanate and anhydrous ethanol hydrolyzed is added to the SiO2 colloidal crystal template, and a sol-gel preparation technique is used to prepare a TiO2-SiO2 photocatalyst with a TiO2 coating on SiO2 spheres, comprising: Adding the mixed solution of the hydrolyzed butyl titanate and the anhydrous ethanol and polyvinyl pyrrolidone to the SiO2 colloidal crystal template, sealing and stirring, and continuing stirring after the ultrasonic dispersion set time to obtain a stable suspension; The suspension is allowed to stand to obtain a layered liquid; Drying the layered liquid, crushing and grinding it into powder to obtain an intermediate powder; The intermediate powder is calcined at high temperature to obtain the TiO2-SiO2 photocatalyst.

8. The sol-gel preparation method of TiO2-SiO2 photocatalyst according to claim 7, characterized in that: The ultrasonic dispersion setting time is at least 15 minutes, the static treatment time is at least 1 hour, the high-temperature calcination temperature is 600° C., and the high-temperature calcination time is 6 hours.

9. Use of the TiO2-SiO2 photocatalyst prepared by the sol-gel preparation method of the TiO2-SiO2 photocatalyst according to any one of claims 1 to 8 in degrading dyes.

10. Use of the TiO2-SiO2 photocatalyst in dye degradation according to claim 9, characterized in that: The dye is dispersed in a dye solution, which is a Rhodamine B solution. The initial concentration of the Rhodamine B solution is 8.43 mg / L, the pH value of the solution is 5.6, and the amount of the TiO2-SiO2 photocatalyst used is 0.20 g.

Citation Information

Patent Citations

  • SiO2-TiO2 composite nanomaterial of core-shell structure and preparation method and application thereof

    CN104998629A